The Effectiveness of Inquiry Learning Model In Chemistry Learning To Improve Students' Critical Thinking: Literature Review - Muzainah, Muzainah; Muntholib, Muntholib; Munzil, Munzil (Universitas Negeri Malang, 2023)
Training students' critical thinking skills cannot be done with one-way learning because learning focuses only on the teacher. The inquiry learning model is very common for teachers because it involves students directly to conduct inquiries. This study aims to determine the influence of the inquiry learning model in chemistry learning to improve students' critical thinking. This study used the SLR (Systematic et al.) method. Data sources were obtained from articles, research journals, and electronic databases such as ERIC, Google Scholar, and Taylor & Francis. The variables used in this study are the dependent variable, namely the ability to think critically, and the independent variable, namely the inquiry learning model. Data is obtained through literature studies by capturing reputable and accredited national and international articles following the criteria studied. Twelve articles were obtained and then analyzed one by one. Each article briefly describes the results of its research. Student success with the inquiry learning model is seen from the increase in students' critical thinking skills. The study found that the inquiry learning model increased student competence, interest in learning, motivation, and critical thinking skills. The inquiry learning model can create a more active learning atmosphere to make learning more meaningful.